1994
DOI: 10.2307/2951512
|View full text |Cite
|
Sign up to set email alerts
|

Discrete and Continuous Choice, Max-Stable Processes, and Independence from Irrelevant Attributes

Abstract: The Generalized Extreme Value Model was developed by McFadden for the case with discrete choice sets. The present paper extends this model to cases with both discrete and continuous choice sets and choice sets that are unobservable relative to the analyst. We also propose behavioral assumptions that justify random utility functions (processes) that have a max stable structure i.e., utility processes where the finite dimensional distributions are of the multivariate extreme value type. Finally we derive non-par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
121
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 20 publications
0
121
0
Order By: Relevance
“…A justification for the structure (2.3) is given in Dagsvik (1994). There it is demonstrated that under Assumption 2, if the choice among jobs satisfies the IIA property then particular structure on the particular structure of the marginal intensity measure of ε(z), ε -2 dε, in (2.3) follows.…”
Section: Assumptionmentioning
confidence: 99%
See 3 more Smart Citations
“…A justification for the structure (2.3) is given in Dagsvik (1994). There it is demonstrated that under Assumption 2, if the choice among jobs satisfies the IIA property then particular structure on the particular structure of the marginal intensity measure of ε(z), ε -2 dε, in (2.3) follows.…”
Section: Assumptionmentioning
confidence: 99%
“…In other words, g(h, w)dhdw yields the probability that a market opportunity with Dagsvik, 1994). The term θ 1 can be interpreted as the fraction of the feasible opportunities that are market opportunities.…”
Section: Assumptionmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, a low probability will be indicated for goods with undesirable X j and/or small ε ij . The issue of individual C i 's is perhaps even clearer here as different 14 Considerable more flexibility with respect to needing to observe actual choice sets is possible, if one makes the assumption that an individual's utility from an alternative has a true random component (Dagsvik, 1994). 15 It is always useful to allow the possibility that the two parameter vectors are statistically equivalent.…”
Section: Discrete Casementioning
confidence: 99%